Living will and advance directives - Ruiz Morollón, Fernando (Revista de derecho aragonés, 2022)
I have three purposes through this small publication: (I) Possible reforms of the Regional Law of Aragón and Administrative Law. (II) Showing preference for notary document, highlighting its advantages in terms of legal security over the administrative document. (III) Criticizing those aspects that, from a practical point of view, make it difficult to prepare these documents. I will try to fulfill the three purposes by relating Notarial Law, Regional Law of Aragón and Administrative Law.
Keywords: Notary public; Regional Law of Aragón; Advance directive; Health Law; Living will; Notary document; euthanasia